Time and Dose Dependent Effects of Adipose-Derived Stromal Vascular Fraction Exosomes on Human Dental Pulp Stem Cell Proliferation - Alinda, Sylva Dinie; Margono, Anggraini; Julianto, Indah; Bagio, Dini Asrianti (UI Scholars Hub, 2026)
Background: Cell proliferation is essential for tissue repair and immunomodulation in regenerative dentistry. Adipose-derived stromal vascular fraction (AD-SVF) is a promising autologous source for tissue engineering. Its exosomes (AD-SVF Exo), as cell-free products stable under ischemic conditions, represent an ethical and attractive modality for dental tissue regeneration and broader regenerative applications. Prior study indicates that AD-SVF Exo can enhance human dental pulp stem cell (hDPSC) migration and proliferation, particularly at low concentrations, but their detailed time- and dose-dependent proliferative effects remain unclear. This study aimed to investigate the time- and dose-dependent effects of low-concentration AD-SVF Exo on hDPSC proliferation in vitro. Methods: AD-SVF exosomes were isolated by size-exclusion chromatography and characterized by flow cytometry and nanoparticle tracking analysis, then applied to hDPSCs at multiple concentrations. Proliferation was evaluated using the Cell Counting Kit-8 assay. One-way ANOVA with LSD post hoc testing was performed (α = 0.05). Results: AD-SVF exosomes (mean size 103 ± 24 nm) expressed CD9 and CD63. All tested concentrations significantly increased hDPSC proliferation versus control in a time- and dose-dependent pattern, with lower doses generally producing the most favorable responses. Conclusions: AD-SVF exosomes enhance hDPSC proliferation in a time- and dose-dependent manner, supporting their potential as a cell-free adjunct in regenerative dentistry.